A Varied Presentation of Tuberous Sclerosis - Saraswoti Dhungana; Manisha Chapagain; Pratikchya Taluchan; Kabin Man Dangol (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 88-90